O uso da multimistura no contexto da segurança alimentar - Kaminski, Tiago André (2007)
A significant part of the Brazilian population is malnourished and philanthropic entities have stimulated the use of multi-mixture as a dietary supplement to change this situation. Although the satisfactory results published by these entities, scientific works do not have demonstrated the multi-mixture effectiveness. Other restrictions to the use the multi-mixture as a supplement are the possible presence of some toxic and/or antinutritional factors in its composition and not appropriate hygienic conditions during the multi-mixture preparation. The aim of this work was to evaluate the chemical and mineral composition and the sanitary condition of twenty multi-mixture formulations. Using laboratory rats, the nutritional quality was evaluated in three samples. The multi-mixture samples presented high levels of fiber and minerals, but only 65% of the samples were considered as source and 10% as high level of manganese to 10 year-old children, based on in 5% dietary supplement and diary ingestion recommendation. The maximum Brazilian legislation limits of cyanic acid, aflatoxins, acidity and oxidative processes were not overcame in all samples analyzed. It was detected microorganism presence overcoming the legislation limits to children foods in 50% of the samples. The best multi-mixture formulation in the biological test was that using legumes and cereal ingredients compared with other two using high level of meals or cereal flours.